A Multicriteria Optimization Approach to the Synthesis of Shale Gas Monetization Supply Chains - Al‐Douri, Ahmad; Sengupta, Debalina; El‐Halwagi, Mahmoud M (Natural Gas Processing from Midstream to Downstream, 2019)
The aim of this chapter is to provide an optimization approach to the design of shale gas monetization networks. Various feedstocks, conversion technologies, and candidate products are simultaneously considered. A superstructure representation is developed to embed alternate configurations and interconnections of the supply chains. A mixed‐integer nonlinear programming formulation is devised to synthesize, screen, and select the monetization network. An economic objective function is used subject to safety and environmental constraints. Other constraints include technical, economic, safety, and environmental performance of the monetization technologies and mass balances for the interconnection among the feedstocks, conversion plants, and products while accounting for feedstock availability, plant capacity limitations, and market demands. A case study is solved for the Barnett and Eagle Ford shale formations. Sensitivity analysis is used to assess the impact of several parameters on the optimal solution.